Activity and Safety of Bevacizumab Plus Fotemustine for Recurrent Malignant Gliomas. (3rd May 2014) - Vaccaro, V.; Fabi, A.; Vidiri, A.; Giannarelli, D.; Metro, G.; Telera, S.; Vari, S.; Piludu, F.; Carosi, M. A.; Villani, V.; Cognetti, F.; Pompili, A.; et al.
Abstract : Background . No established chemotherapeutic regimen exists for the treatment of recurrent malignant gliomas (rMGs). Herein, we report the activity and safety results of the bevacizumab (B) plus fotemustine (FTM) combination for the treatment of rMGs. Patients and Methods . An induction phase consisted of B 10 mg/kg days 1, 15 plus FTM 65 mg/m 2 days 1, 8, and 15. Nonprogressive patients entered the maintenance phase with B 10 mg/kg plus FTM 75 mg/m 2 every 3 weeks. The primary endpoint was response rate; secondary endpoints included safety, progression free survival (PFS), and overall survival (OS). Results . Twenty-six patients affected by recurrent MGs (50% glioblastoma) were enrolled. Eight partial responses (31%) were observed. Median PFS and OS were 4 (95% C.I.: 2.8–5.1) and 6 months (95% C.I.: 4.2–7.8), respectively. Responses were significantly associated with both improved PFS and OS (P = 0.002 and P = 0.001, resp.). Treatment adverse events were mostly mild to moderate in intensity. Bevacizumab-related adverse events included grade 3 venous thromboembolic event (8%), grade 2 epistaxis (4%), hypertension (8%), and gastrointestinal perforation (4%). Conclusions . Bevacizumab plus FTM showed activity and good tolerability in pretreated MGs. Further investigations are needed in order to verify the benefits deriving from the addition of B to a cytotoxic in this clinical setting of patients.